Light Supremacy vis-à-vis Non-White Immigrants as Racism in the 21st Century: A Question of Color - Ronald E. Hall (European Scientific Journal, ESJ, 2016)
Racism focuses attention upon African-Americans assumed victimized by Euro-Americans as an outcome of White supremacy. The recent trend in immigration by light-skinned non-White immigrants sustains racism via light supremacy. Distinct from racism per se White supremacy is contingent upon race, racism per light supremacy is contingent upon skin color. Demonstration of light supremacy is referenced in civil litigation and government hate crime statistical data. The most dramatic illustration of light supremacy as racism is referred to as “brown racism.” As suggested by Washington, brown racism is perpetrated by Mestizos, Chinese, Filipinos and South Asians against dark-skinned, persons particularly AfricanAmericans. Considering definition light supremacy is a product of White supremacy attributed to the aftermath of European conquest and/or domination. Lacking acknowledgement of light supremacy as a product of White supremacy will then sustain racism well into the 21st century and beyond if not immediately and effectively challenged by the Sociology academy.